Against administrative criminology - Galliher, John F. (Social justice, 1999)
Part of a special issue celebrating 25 years of this journal. The writer presents a critique of “administrative criminology,” which is consistent with the requirements of government bureaucrats. He argues that mainline criminology became separated from the study of the state. He argues that this was due, in part, to the government's sponsorship of criminal justice programs through the Law Enforcement Assistance Association. He concludes that without this journal, there would be very few outlets in academic criminology for analysis of oppressive drug laws, racist police, and a prison system that is a leader in incarceration rates.